Efflux pump-mediated resistance to antifungal compounds can be prevented by conjugation with triphenylphosphonium cation - Wenqiang Chang (Nature Portfolio, 2018)
Antifungal resistance due to upregulation of efflux pumps is common in Candida albicans. Here, the authors show that conjugation with mitochondria-targeting triphenylphosphonium cation can enhance or restore the antifungal activity of potential efflux pump substrates.